(untitled) (International journal of artificial intelligence, 2026)
The article describes the features of the cultural and spiritual heritage of the Uzbek people, the views of thinkers on ecological culture, in forming positive views and attitudes of primary school students towards nature, eliminating environmental problems, and instilling ecological education in the minds of primary school students.